Kesalehan KESALEHAN SOSIAL MENURUT MATIUS 23 : Konstruksi Etika Kristen Untuk Penatalayanan Adaptif Muda-mudi Gereja dalam Ruang Media Sosial - Bestian Simangunsong; Erman Saragih; Frimus Y Nababan; Jihan Panggabean; Lukas Van El Manik (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
Changes in social behavior and the increasing presence of church youth in the social media space are certainly a challenge for the church. The purpose of this study is to describe the construction of Christian ethical principles on social piety based on the reading of Matthew 23 as a concept of adaptive stewardship for Christian youth. The method used is descriptive qualitative with critical and constructive studies of Matthew 23 and Christian youth stewardship. The conclusion is social piety is a construction of Christian ethics from reading the interpretation of Matthew 23. The social piety in question includes four principles of Christian ethics for young Christians when they are present in the social media space, namely first, social media as a place to express Christian integrity and identity. (Vv. 1-4); second, social media as a place to sow and transmit the values ​​of honesty (Vv. 5-6); third, social media as a forum to build brotherly solidarity and equality (Vv. 7-12); four social media as a place to convey the prophetic voice (Vv. 13-36).